Evaluating the Relationship between Parental Emotional Attachment and Online Crime Victimisation: A Study of University Students in Kenya, A Case of Chuka University (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Online crime victimisation harms not only individuals but also the wider community by weakening trust and safety. This study looked at how parental emotional attachment influences the chances of online crime victimisation among university students at Chuka University in Tharaka-Nithi County, Kenya. The target population was 19650 students pursuing different courses in Chuka university. Participants were randomly sampled from the population after the pilot study which was conducted in Tharaka University. During the pilot study, the reliability of research instruments was measured (Cronbach Alpha of .87) and deemed valid to collect actual data. This study relied on the principles of Routine Activity Theory and Social Learning Theory. After seeking permission from relevant authorities such as Tharaka University Ethics Committee, NACOSTI and Chuka University management the researcher proceeded to collect the actual data from 155 students using questionnaires by physically visiting the lecture hall. After inferential data analysis the results showed strong links between weak parental bonds and higher vulnerability to online victimisation. Maternal attachment (ρ = .554, p < 0.01) and paternal attachment (ρ = .483, p < 0.01) both played important roles in shaping how safe or at-risk youths were online. In today’s world, digital technologies bring both opportunities and risks. The findings show that parental emotional support remains a strong shield even in an age where artificial intelligence, social media, and online platforms shape young people’s lives. By using technology in education, counselling, and law, society can build new ways to protect and guide youths. The study concludes that strengthening parental support, building emotional resilience, and encouraging self-control can lower the chances of online victimisation. At the same time, digital tools such as online safety training, mental health support apps, and technology-informed laws can help create safer spaces. Working together, parents, teachers, and policymakers can use these tools to protect young people and support sustainable development in line with the wider goal of building safer and more inclusive societies.